Exact and numerical soliton solutions of some nonlinear physical models - Kaya, D (Elsevier Science Inc, 2004)
We consider two types of variant water wave equations and the solitary wave solutions of them are constructed by using the Adomian decomposition. We also made a numerical comparison of the equations. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: the Adomian decomposition method; water wave equation; A solitary wave solution; the self-cancelling noise terms